(untitled) - Arturu, Anna Minja (Cần Thơ, 2019)
This study was conducted to assess the dynamics of microbial quality and safety of frozen Pangasius fillet throughout processing and to understand the transmission routes of bacteria during the handling of Pangasius products.
Keywords: Food industry and trade,Công nghiệp thực phẩm và thương mại